Ardistomis quixotei (Coleoptera: Carabidae: Clivinini), a new species from Cuba and Mexico: structural and habitat features of adults, larvae and pupae, comparisons with previously described species, and notes about classification and biogeography - R., Pavel Valdés (Zootaxa, 2007)
A new species of the genus Ardistomis Putzeys, A. quixotei, is described and illustrated from specimens collected in Cuba and Mexico, along with its larva and pupa. Data on natural history and habitat are given for Cuban populations. A key to adults of all species of Ardistomis from the West Indies is included. Among the species studied for comparison, A. elongatulus Putzeys and A. schaumi LeConte seem to be the closest Middle American relatives of A. quixotei, based on features of the male genitalia. Larval features support recognizing the ardistomines (Ardistomis Putzeys, Semiardistomis Kult, and Aspidoglossa Putzeys) as a subtribe of the tribe Civinini. Ardistomis quixotei probably extended its geographical range to Cuba from Mexico during the Quaternary Period.Una nueva especie del género Ardistomis Putzeys, A. quixotei se describe e ilustra a partir de especimenes colectados en Cuba y México junto a las larvas y pupas. Se ofrecen datos de la historia natural y el hábitat para las poblaciones cubanas. Se incluye una clave para determinar los adultos de todas las especies antillanas del género Ardistomis. De las especies Centro Americanas estudiadas para comparar, A. elongatulus Putzeys y A. schaumi LeConte parecen ser las más cercanamente relacionadas de A. quixotei, basado en características de los genitales masculinos. Las características larvales apoyan la clasificación de los Ardistominos (Ardistomis Putzeys, Semiardistomis Kult, y Aspidoglossa Putzeys) como una subtribu de la tribu Clivinini. Ardistomis quixotei extendió su rango geográfico hacia Cuba desde México durante el período Cuaternario.